2000
DOI: 10.1002/1521-3765(20000717)6:14<2644::aid-chem2644>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Study of the Acetohydroxamic Acid Protonation: The Solvent Effect

Abstract: The mechanism of the protonation of acetohydroxamic acid is investigated comparing experimental results and ab initio calculations. Experimentally, the UV spectral curves were recorded at different temperatures, at constant dioxane/water concentration, and at very high concentrations of strong mineral acids. The process is followed by monitoring the changes in the UV curves with increasing acid concentration. The molecular structures and the solvation energies were calculated with the RHF, B3LYP, and MP2 metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Recently, a theoretical and experimental study of the solvent effect on its protonation has been carried out. 20 A similar trend in energy is observed in the case of these two molecules, with the energy gap between the 1E and 1Z forms becoming smaller with each substitution (see Table 6), until for propanohydroxamic acid, the 1E form becomes favored over 1Z. The basis set dependence of the calculations is again reflected in the fact that calculations with the 6-31G* basis set favor the 1Z isomer by 0.9 kcal mol Ϫ1 .…”
Section: Aceto-and Propanohydroxamic Acidssupporting
confidence: 62%
“…Recently, a theoretical and experimental study of the solvent effect on its protonation has been carried out. 20 A similar trend in energy is observed in the case of these two molecules, with the energy gap between the 1E and 1Z forms becoming smaller with each substitution (see Table 6), until for propanohydroxamic acid, the 1E form becomes favored over 1Z. The basis set dependence of the calculations is again reflected in the fact that calculations with the 6-31G* basis set favor the 1Z isomer by 0.9 kcal mol Ϫ1 .…”
Section: Aceto-and Propanohydroxamic Acidssupporting
confidence: 62%
“…18 The intensity of this peak increases with an increase of AHA concentration, while the position remains unchanged. These assignments are supported by previous studies, [19][20][21] in which it was found that in the sequence from a non-polar solvent to a polar solvent the relative intensity of the absorption band of the C¼N group is lowered; therefore, the enol tautomers of AHA are not likely to be formed in polar solvents such as TBP. Furthermore, the formation of the C¼N enol tautomer structure assumed 17 for hydroxamic acids under alkaline conditions was recently refuted 17 by FT-IR and FT-Raman spectral evidence in both solid and basic solution; therefore, the C¼N enol forms were excluded from the evaluation and discussion in the present paper.…”
Section: Resultssupporting
confidence: 82%
“…A number of theoretical calculations were performed related to the structural analysis of FHA [21][22][23][24][25][26][27][28][29][30][31][32][33] and AHA [34][35][36][37][38][39]. Low-quality calculations suggested that FHA exists preferentially as the 1E-keto isomer with OH bond in anti-orientation in the gas phase [21,25,28,32].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the DFT/B3LYP/6-311++G** and MP2/6-31++G** calculations point out to the 1E tautomer being slightly more stable than the 2Z one [28,32], whereas the calculations at MP2(FC)/6-31G( y ) level within CBS-Q theory [31] indicate the 2Z tautomer to be more stable than the 1E one. The recent MP2 [34,36] and DFT [16] calculations performed for AHA indicated 1Z as the lowest energy isomer, however the two methods differed in the order of stability of the other two lowest energy isomers. MP2 pointed the order of stability to 1Z > 2Z > 1E, whereas DFT to 1Z > 1E > 2Z.…”
Section: Introductionmentioning
confidence: 99%